Creating a healing environment in hospital buildings through day-lighting design - Aripin, Srazali (2010)
In the hospital building, where patients sick medical treatment and hospital staff (doctors and nurses) provide continuous support, creating a healing environment is an imperative. A majority of literature on the healing environment has reached a consensus that the physical aspects of built environment could contribute indirectly to the health outcomes of patients and staff. day-lighting, among others, is considered one of the most influential factors to achieve visual comfort contributing to a healing environment. Therefore, a two-pronged hypothesis is adopted in this paper: (1) visual comfort can be achieved through appropriate day-lighting design strategies. (2) A healing environment is achieved only when the patients are satisfied with the visual comfort in the ward environment. This paper outline the role and importance of physical aspects (i.e. day-lighting) in hospital design. With the theme of 'daylight and health', previous studies related to the factors of the physical environments in hospital buildings that influence health outcome are critically reviewed. The physical factors affecting daylighting to achieve visual comfort are also analysed. Conflicting issues of daylighting: 'physical to physical' (daylight vs. solar heat gain) and 'physical to psychological' (daylight vs. undesirable glare) are discussed. To achieve this, qualitative (observations and questionnaire surveys) and quantitative (measurement) analyses are adopted to examine daylighting conditions in the existing four-bed ward environments of selected public designs in Malaysia. The opinion surveys of the four-target groups (patients, hospital staff, healthcare designers and healthcare providers) will be analysed and the findings will be corroborated by means of field measurements. The paper calls for a comprehensive critical review of the physical aspects, in particular daylighting design, in creating a healing environtment physically and psychologically appropriate in hospital design.